A MIXTURE OF PLANT EXTRACTS CAN BE MORE EFFECTIVE THAN A COMMERCIAL ANTIBACTERIAL FEED ADDITIVE IN POULTRY CHALLENGED WITH CLOSTRIDIUM PERFRINGENS - Eloff, J. N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
To reduce costs in the production of poultry many birds are kept in close proximity. This leads to infections that reduce productivity and antibiotics are given as prophylactics in the feed. This has led to the development of antimicrobial resistance with some evidence that the resistance may be transferred to human bacterial pathogens. The European Union has banned the use of antibiotic feed additives in animal production. One of the solutions to this problem is using plant extracts. Many plant extracts were tested for activity against poultry bacterial pathogens. The mechanism of activity of plant extracts may also be by stimulation of the immune system of the bird or by reducing inflammation due to the activity of gut microorganisms. Antioxidant activity of plant extracts may therefore play a role. An extract of Combretum woodii leaves had good activity against the poultry pathogens and excellent anti-oxidant activity. By simple manipulation of the extracts we could increase the antibacterial and anti-oxidant activity of the crude extract. When it was tested in a small poultry trial, it was relatively toxic to the poultry and in in vivo cellular assays. We then investigated the activity of extracts of several plant species that have been used as human herbal medicines against poultry pathogens. From this we selected two that had good complementary activity against different pathogens. We tested different combinations of these extracts and a grape seed extract with good antioxidant activity in a poultry trial. No significant differences were found between positive controls, negative controls and treatments. The good hygienic conditions under which the bids were kept may have led to decreased infection. Some plant extracts gave statistically signicantly better results than Zn-Bacitracin, the commercially used antibiotic feed additive in birds challenged by infecting with Clostridium perfringens in several performance parameters. The results indicate the potential of using plant extracts to increase animal productivity. Acknowledgement: This work is based on the theses of Theresa Ntloedibe, Havanah Chikoto and Ilse van Heerden. BioPAD an initiative of the Dept of Science and Technology provided funding.